CHALLENGES AND SOLUTIONS IN OVERCOMING FINANCIAL ADMINISTRATION MANAGEMENT OBSTACLES IN SCHOOL ENVIRONMENTS - Melati, Maya Tessa; Simatupang, Azirah Shahieza; Safitri, Dita Ayu; Hidayatullah, Rully (Cahaya Ilmu Bangsa Institute, 2024)
Financial management and educational administration in schools are crucial aspects that affect the quality of educational services. However, many schools face various challenges that hinder the effectiveness of this management. This article aims to identify the main challenges in financial management and educational administration and offers solutions that can be implemented to address these obstacles. The first challenge is the lack of transparency and accountability in financial management. This is often caused by inadequate record-keeping systems and insufficient training for administrative staff. Additionally, many schools are also facing increasing operational costs, making budget management increasingly difficult. Uncertainty regarding funding sources, especially in areas with limited budgets, further complicates this situation. Furthermore, the competence of administrative staff often poses a challenge. Many staff members lack the educational background or training necessary in financial management, leading to errors in budget management. Moreover, the suboptimal use of information technology in some schools hampers efficiency in the collection and analysis of financial data. In addressing these challenges, this article recommends several strategic solutions. First, the implementation of an integrated technology-based financial management system can enhance transparency and accountability. This system allows for real-time monitoring of expenditures and income, as well as facilitating the creation of accurate financial reports.